Chirality Induction and Amplification in the 2, 2, 2‐Trifluoroethanol⋅⋅⋅Propylene Oxide Adduct1. (4th June 2014) - Thomas, Javix; Jäger, Wolfgang; Xu, Yunjie
Abstract Chirality induction and amplification in a model system, that is, the 2, 2, 2‐trifluoroethanol (TFE)⋅⋅⋅propylene oxide (PO) adduct, were investigated using free‐space and cavity‐based Fourier transform microwave spectroscopy, complemented with high level ab initio calculations. Rotational spectra of four out of eight predicted TFE⋅⋅PO adducts were assigned, and the remaining four were shown to relax to the geometries of the four observed in a jet expansion. The g+ TFE⋅⋅⋅S‐PO adduct was found to be favored over that of g− TFE⋅⋅⋅S‐PO by a factor of 2.8 at 60 K. This difference contrasts the TFE dimer for which an extreme case of chirality synchronization was previously reported. All TFE⋅⋅⋅PO conformers observed take on the open arrangement, in contrast to 2‐fluoroethanol⋅⋅⋅PO, which prefers the closed arrangement. Furthermore, perfluorination at CH3 increases the hydrogen‐bonding energy by about 70 % over its ethanol counterpart.